Identifying thresholds to classify moderate-to-heavy soil-transmitted helminth intensity infections for FECPAKG2, McMaster, Mini-FLOTAC and qPCR - Levecke, Bruno (2020)
World Health Organization (WHO) has defined moderate-to-heavy intensity (M&HI) infections with soil-transmitted helminths (Ascaris lumbricoides, Trichuris trichiura and the two hookworms, Ancylostoma duodenale and Necator americanus) based on specific values of eggs per gram of stool, as measured by the Kato-Katz method. There are a variety of novel microscopy and DNA-based methods but it remains unclear whether applying current WHO thresholds on to these methods allows for a reliable classification of M&HI infections. We evaluated both WHO and method-specific thresholds for classifying the M&HI infections for novel microscopic (FECPAKG2, McMaster and Mini-FLOTAC) and DNA-based (qPCR) diagnostic methods. For this, we determined method-specific thresholds that best classified M&HI infections (defined by Kato-Katz and WHO thresholds; reference method) in two multi-country drug efficacy studies. Subsequently, we verified whether applying these method-specific thresholds improved the agreement in classifying M&HI infections compared to the reference method. When we applied the WHO thresholds, the new microscopic methods mainly misclassified M&HI as low intensity, and to a lesser extent low intensity infection as M&HI. For FECPAKG2, applying the method-specific thresholds significantly improved the agreement for Ascaris (moderate → substantial), Trichuris and hookworms (fair → moderate). For Mini-FLOTAC, a significantly improved agreement was observed for hookworms only (fair → moderate). For the other STHs, the agreement was almost perfect and remained unchanged. For McMaster, the method-specific thresholds revealed a fair to a substantial agreement but did not significantly improve the agreement. For qPCR, the method-specific thresholds based on genome equivalents per ml of DNA moderately agreed with the reference method for hookworms and Trichuris infections. For Ascaris, there was a substantial agreement. We defined method-specific thresholds that improved the classification of M&HI infections. Validation studies are required before they can be recommended for general use in assessing M&HI infections in programmatic settings.